PREDIKSI POLA DAN JUMLAH PERGERAKAN BARANG DI PROVINSI LAMPUNG - Junaedi, Tas'an (UNIVERSITAS LAMPUNG, 2013)
The transportation of goods between Sumatra and Java using the highway mode that accumulatewith local transportation will greatly burden roads in Lampung province. This research was con -ducted to predict the pattern and amount of movement of goods in the future. The modelling isconducted for the plan period up to 20 years based on growth predictions of geographical, social,economic and traffic flow. This study conducted a process of Sequential Demand Model (PlanningModel 4 stages) by using software Transplan Version 8.Transportation patterns in 2030 is predicted will be dominated by continuous trips withdomination of movement from Java to South Sumatra, or otherwise. Both the transportationbetween internal zones and external zone to internal zone have a significant increase. The moststrategic main line freight in Lampung for today and in the future is along the Bakauheni-SouthSumatra and Bengkulu-South Sumatra both through toll roads, national roads, and railways.